Platinum (Pt): Metal complexes and their applications against cancer (Research, Society and Development, 2025)
The present article discusses introductory aspects of the coordination chemistry of platinum complexes, especially platinum(II) and platinum(IV), and the use of these complexes in the treatment of cancer. Considering the historical and current relevance of the metal complex known as “cisplatin” and its analogues, its mechanisms of action, potentialities, and limits of action are evaluated, in addition to the known adverse reactions to higher doses and/or prolonged use. The objective of this article is to discuss, through a bibliographic review, the fundamental aspects of the coordination chemistry of Platinum (Pt), especially the chemistry of the metal complex known as “cisplatin” and its analogues and successors as anticancer agents. The mechanism of action in the biological environment is analyzed, as well as possible therapeutic strategies aiming at greater efficacy in combating cancer cells. Finally, some future perspectives for the applications of platinum complexes in the treatment of different types of cancer are presented.